Assessing the stock status of Megalaspis cordyla in the northern Arabian Sea: a multi-model approach for sustainable fishery management - Kalhoro, Muhsan Ali; Sun, Jing; Zhu, Lixin; Liang, Zhenlin; Liu, Chunli; Raza, Hasnain (Frontiers in Marine Science, 2025)
Effective fisheries management is crucial for the sustainable use of fishery resources, increasing relying on stock assessments. The Megalaspis cordyla an economically important fish species in Pakistan, require an accurate assessment of its current biomass to take effective management strategies. This study utilized stock assessment techniques, including the Catch-Based Monte Carlo Maximum Sustainable Yield (CMSY), length-based Bayesian Biomass (LBB), Just Another Bayesian Biomass Assessment (JABBA), and ARIMA models. While CMSY, BSM, JABBA, ARIMA rely on annual catch-effort data, while LBB analyzes length-frequency data along with resilience inputs. An analysis of 15 years of catch data (2007-2021), and 1,442 length-frequency data from Pakistani waters revealed that the fishery is overfished both in terms of exploitation and biomass (LBB at F/M = 1.6, B/BMSY = 0.76 and B/B0 = 0.27). The CMSY method estimated biological reference points as r = 0.53, k = 231, and a maximum sustainable yield (MSY) of 3.06. In comparison, the BSM provide values of r =0.03, k =271, MSY = 2.56. The JABBA model estimated MSY of 3.637, with a biomass to MSY2021 (B2021/BMSY) of 0.68 and F2021/FMSY of 1.56, indicating excessive exploitation. The projected biomass ratio (B2021/BMSY) of 0.798, is<1, confirms overexploitation. Additionally, the ARIMA (2, 0, 1) model, demonstrated the lowest mean square error, predicts a significant upward trend in fish catches in the near future. The findings across all models consistently indicate that the M. cordyla fishery is overfished, with current catches exceeding sustainable limits. Biological reference points from CMSY, JABBA, and LBB models, all below 1.0, underscore the unsustainable of the fishery. If current trend continues, the fishery faces a substantial risk of collapse. To mitigate this, immediate management measures should be implemented to promote the sustainable utilization of this critical fishery resource in Pakistan.